UPAYA MEMBANGUN PEMAHAMAN PUBLIK TENTANG PENTINGNYA HAK PILIH MELALUI SOSIALISASI PILKADA 2024 DENGAN KOLABORASI TRIDARMA PERGURUAN TINGGI - Ansari; M. Fadly Syahputra; Nurul Asri, Yoana (Forum Komunikasi Dosen, 2024)
This Community Service Program (PKM) aims to enhance public understanding of the importance of voting rights in the 2024 Regional Head Election (Pilkada), involving the active role of higher education institutions through the three pillars of collaboration. The event was attended by one hundred lecturers lecturers from the Forum of Communication of Lecturers (FKD) across West Java, discussing the importance of book publication as an educational medium for young voters on democracy and voting rights. The implementation method included preparation, interactive execution, and evaluation through post-event discussions. The participants showed high enthusiasm, asking numerous questions related to textbook writing strategies, publisher selection, citation improvement, collaboration between higher education institutions, and book marketing strategies. As a result, the event not only provided education on the importance of creating textbooks and reference books but also raised lecturers' awareness of their role in facilitating political and democratic education. It also opened opportunities for collaboration to expand the impact of democratic education through informative and sustainable textbook publications.